Induction of Oxidative Stress Through Inhibition of Thioredoxin Reductase 1 Is an Effective Therapeutic Approach for Hepatocellular Carcinoma - Lee, Derek; Xu, Iris Ming‐Jing; Chiu, David Kung‐Chun; Leibold, Josef; Tse, Aki Pui‐Wah; Bao, Macus Hao‐Ran; Yuen, Vincent Wai‐Hin; Chan, Cerise Yuen‐Ki; Lai, Robin Kit‐Ho; Chin, Don Wai‐Ching; Chan, Daniel For‐Fan; Cheung, Tan‐To; et al. (Hepatology (Baltimore, Md.), 2019)
Hepatocellular carcinoma (HCC) is one of the most prevalent and lethal cancers worldwide which lacks effective treatment. Cancer cells experience high levels of oxidative stress due to increased generation of reactive oxygen species (ROS). Increased antioxidant‐producing capacity is therefore found in cancer cells to counteract oxidative stress. The thioredoxin system is a ubiquitous mammalian antioxidant system which scavenges ROS, and we demonstrate that it is vital for HCC growth as it maintains intracellular reduction‐oxidation (redox) homeostasis. Transcriptome sequencing in human HCC samples revealed significant overexpression of thioredoxin reductase 1 (TXNRD1), the cytosolic subunit and key enzyme of the thioredoxin system, with significant correlations to poorer clinicopathological features and patient survival. Driven by the transcriptional activation of nuclear factor (erythroid‐derived 2)–like 2, the master protector against oxidative stress, TXNRD1 counteracts intracellular ROS produced in human HCC. Inhibition of TXNRD1 through genetic inhibition hindered the proliferation of HCC cells and induced apoptosis in vitro. Administration of the pharmacological TXNRD1 inhibitor auranofin (AUR) effectively suppressed the growth of HCC tumors induced using the hydrodynamic tail vein injection and orthotopic implantation models in vivo. Furthermore, AUR sensitized HCC cells toward the conventional therapeutic sorafenib. Conclusion: Our study highlights the reliance of HCC cells on antioxidants for redox homeostasis and growth advantage; targeting TXNRD1 resulted in dramatic accumulation of ROS, which was found to be an effective approach for the suppression of HCC tumor growth.